Parasitological Indices of Malaria Transmission in Children under Fifteen Years in Two Ecoepidemiological Zones in Southwestern Burkina Faso - Aristide S. Hien; Ibrahim Sangaré; Sanata Coulibaly; Moussa Namountougou; Léa Paré-Toé; Anicet Georges Ouédraogo; Abdoulaye Diabaté; Brian D. Foy; Roch K. Dabiré (Journal of Tropical Medicine)
Twenty years after the latest publications performed on the parasitological indices of malaria transmission in northwest of the second city of Burkina Faso, it was important to update the epidemiological profile of malaria in children under the age of 15 years. The objective of this study was to determine and compare the parasitological parameters of malaria transmission by season, area, and age in the two zones (rice and savanna) in the northwest of Bobo-Dioulasso, Burkina Faso. Overall, the results showed that there was no significant difference in the parasitological indices of malaria transmission within children under fifteen years between the rice site and the savannah site and whatever the season (P>0.05). The profound environmental modifications that occurred in the rice zone would have led to changes in vector behavior and consequently to changes in the epidemiological profile of malaria, contrary to the results obtained since the last publications. An entomological study correlated with this study is therefore necessary for effective decision-making for the malaria control in both areas. Future research must now focus on the impact that these profound environmental modifications of rice area are having on malaria control in Burkina Faso.